Modeling and properties of glass fibre-reinforced nylon - Nurizzathanis, Mohamad Kusaseh (2015)
Nylon is one of the synthetic polymers family that known as polyamides. This research study is about to analyze the modeling and properties of glass fibre-reinforced nylon. In spite of many advantages of plastics, the better physical and mechanical properties of plastic are needed. So that, reinforced plastics (composites plastics) has produced. The objectives of this study is to analyze process flow of plastic part modeling for injection molding process by using Autodesk Moldflow Insights software, to fabricate the plastic part of glass fibre-reinforced nylon by using injection molding machine, and to study the mechanical properties of glass fibre-reinforced nylon. Specimens of dog bone shaped with standard size ASTM D638 are used specifically in order to carry out this research. The processes involved in this research study are moldflow analysis, injection molding process, and tensile strength test. Moldflow analysis is used to identify the suitable process flow of injection molding process. The 3D modeling of dog bone shape specimen is used in completing the moldflow analysis. Then, the injection molding machine is used to produce the glass fibre-reinforced nylon dog bone shape specimen with different percentage of glass fibre. The glass fibre percentages used are 5%, 10%, 15%, and 20%. The mixtures were injected with a range of temperature of 210°C-255°C throughout the barrel. Lastly, the universal tensile machine is used to generate a tensile stress-strain graph for every specimens and the tensile strength of the testing parts is analyzed. As a result, it is concluded that the specimen with higher percentage of glass fibre-reinforced nylon that exceeds the percentage of pure nylon obtain high tensile stress at maximum temperature. This is due.to the higher amount of weight of glass fibre-reinforced nylon increased as the percentage increased. The differences tensile strength between pure nylon and glass-fibre reinforced is tabulated and plot in a graph.